2021
DOI: 10.1136/bmjopen-2020-041179
|View full text |Cite
|
Sign up to set email alerts
|

Which came first, obstructive sleep apnoea or hypertension? A retrospective study of electronic records over 10 years, with separation by sex

Abstract: ObjectivesObstructive sleep apnoea (OSA) is a risk factor for hypertension (HTN), but the clinical progression of OSA to HTN is unclear. There are also sex differences in prevalence, screening and symptoms of OSA. Our objective was to estimate the time from OSA to HTN diagnoses in females and males.DesignRetrospective analysis of electronic health records (EHR) over 10 years (2006–2015 inclusive).SettingUniversity of California Los Angeles (UCLA) Health System in Los Angeles, California, USA.Participants4848 p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…However, an alternative explanation, although less likely, for the lack of association between OSA and arterial stiffness/increased PP in our study may be the fact that polygraphy and brachial BP measurement were performed in the same setting and explored in a cross‐sectional fashion. It is known that following the OSA screening and diagnosis, it may take months or years until the development of incident hypertension, 23 and resultant targert arterial damage. It has been shown that patients diagnosed with OSA at an older age have longer time duration since the prior hypertension diagnosis and less time to a subsequent hypertension diagnosis 23 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, an alternative explanation, although less likely, for the lack of association between OSA and arterial stiffness/increased PP in our study may be the fact that polygraphy and brachial BP measurement were performed in the same setting and explored in a cross‐sectional fashion. It is known that following the OSA screening and diagnosis, it may take months or years until the development of incident hypertension, 23 and resultant targert arterial damage. It has been shown that patients diagnosed with OSA at an older age have longer time duration since the prior hypertension diagnosis and less time to a subsequent hypertension diagnosis 23 …”
Section: Discussionmentioning
confidence: 99%
“…It is known that following the OSA screening and diagnosis, it may take months or years until the development of incident hypertension, 23 and resultant targert arterial damage. It has been shown that patients diagnosed with OSA at an older age have longer time duration since the prior hypertension diagnosis and less time to a subsequent hypertension diagnosis 23 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations